COMPARATIVE STUDY OF USING DRAMA AND SIMULATION TECHNIQUES TOWARD STUDENTS’ SPEAKING ABILITY - Eva Faliyanti; Nanda Habib Firdaus (UAD TEFL International Conference)
Speaking is one of the productive skills in English. It acts as an important skill which becomes a depiction of students' result in studying English. Oftentimes, English ability is measured by their speaking because it serves a tool of communication which represents the major interaction with other people. But in fact, the condition of a learning process in a sphere of speaking has not supported students to master speaking ability yet. The application of techniques and methods are actually not interesting enough to attract them. Students tend to be passive when they are in learning about material related to speaking.The objectives of this research are; to find out students' speaking score by applying drama technique; to find out students' score by using simulation technique; to find out whether the drama is better than simulation technique in increasing students' speaking ability. The population of this research is 37 students in the fourth semester of English Department at the Muhammadiyah University of Metro. The researcher conducts systematic random sampling design and pre-test and post-test control group design as a research instrument. The result of hypothesis test on test phases both provides the different result which uses 5% significant degree, where a count is higher than t -table on the analysis data of post-test with t-count =2,36  and t-table =2,12. It shows that the students who are taught by drama technique having a higher score. In conclusion that drama technique is more effective than simulation technique in term of students' speaking ability.